ANALISIS KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN KONSUMEN PADA PT ASTRA INTERNATIONAL DAIHATSU BANJARMASIN - Kukun Kunaini; Sudirwo Sudirwo (KINDAI, 2022)
This study aims to analyze the quality of service in increasing customer satisfaction at PT Astra International Daihatsu Banjarmasin. This type of research uses descriptive quantitative. Data analysis techniques used are interviews, observations, and questionnaires with a research time of more than 2 months with 100 respondents. The problem that has been obtained so far is the lack of service provided by employees in the workshop, where employees seem indifferent to customers. In addition, there are often complaints such as delays in the delivery of cars that have been repaired, delays in service and repair, spare parts that are difficult to find so that cars need to be repaired longer, and mechanics who are less friendly and polite to consumers. The results of this study are that PT Astra International Daihatsu Banjarmasin has not carried out the service quality that it should have, which so far has not fulfilled the 10 dimensions that should have. So, this research can help PT Astra International Daihatsu Banjarmasin to more optimally serve customers with the 10 dimensions that have been suggested.